Cariogenic and erosive potential of industrialized fruit juices available in Brazil - Leopoldina de Fátima Dantas de Almeida; Gisely Maria Freire Abílio; Mônica Tejo Cavalcante; Ricardo Dias Castro; Alessandro Leite Cavalcanti (Universidade Estadual de Campinas, 2015)
Aim: This in vitro study evaluated the cariogenic and erosive potential of different industrialized fruit juices available in the Brazilian market. Methods: Twenty-five samples of fruit juices were analyzed physically and chemically by means of the following parameters: pH, titratable acidity (TA) and total soluble solid content (TSSC), reducing sugars (e.g.: glucose), non-reducing sugars (e.g.: sucrose) and total sugars. The analyses were made in triplicate. Data were collected by a single examiner and were recorded in study-specific charts. Data were statistically analyzed by ANOVA and Tukey's post-test (p<0.05). Results: All fruit juices showed pH below the critical value of 5.5, with significant differences among the samples (p<0.0001). Mango juice (Jandaia®) presented the lowest TSSC (10.25 oBrix), while orange juice (Del Valle®) presented the highest TSSC (12.75 o Brix), with no significant differences among the samples. The lowest and the highest TA values were recorded for cashew juice (Jandaia®) (0.13%) and passion fruit (Del Valle®) (0.52%), respectively (p<0.0001). For reducing sugars (glucose), the highest value was recorded for purple fruit juice (Skinka®) (10.85 g/100mL) and the lowest was recorded for strawberry juice (Kapo®) (1.84 g/100mL). Regarding non-reducing sugars (sucrose), the values ranged from 0.45 g/100mL (passion fruit/Del Valle®) to 9.07 g/100mL (orange/Del Valle®). Purple fruit juice (Skinka®) presented the highest total sugars content (12.09 g/100mL), while guava juice (Jandaia®) presented the lowest content (7.25 g/100mL). There were significant differences among the samples for reducing, non-reducing and total sugars (p<0.0001). Conclusions: The industrialized fruit juices evaluated in this study presented low pH and a high total sugar content, differing in their erosive and cariogenic potential, respectively.